Identification and cytotoxic evaluation of the novel rutin–methylglyoxal adducts with dione structures in vivo and in foods. (30th May 2022) - Chen, Min; Zhou, Hua; Huang, Caihuan; Liu, Pengzhan; Fei, Jia; Ou, Juanying; Ou, Shiyi; Zheng, Jie
Graphical abstract: Highlights: Rutin eliminated methylglyoxal (MGO) by the formation of adducts. Rutin–di-MGO adducts with dione structures were identified for the first time. These oxidized rutin–di-MGO adducts were detected both in foods and in vivo . The adducts displayed lower cytotoxicities than MGO in various cell lines. Abstract: Flavonoids with meta -hydroxyl groups have been proven to react with methylglyoxal (MGO) and form mono- and di-MGO adducts via nucleophilic addition reactions. Rutin, a rutinoside of quercetin with typical meta -phenol structure, is widely distributed in plant-sourced materials. Interestingly, different from the adducts reported between flavonoids and MGO, new rutin–MGO adducts with dione structures on the moiety of MGO were identified and proven to occur in various foods (0.66–6.58 mg/kg in total) and in vivo (up to 5.01 μg/L in plasma of rats administered with 100 mg/kg bodyweight of rutin). The three adducts discovered were assigned as 6-(1, 2-propanedione)-8-(1-acetol)-rutin, 6-(1-acetol)-8-(1, 2-propanedione)-rutin, and 6-(1, 2-propanedione)-8-(1, 2-propanedione)-rutin. Cytotoxicity evaluation in different cell lines indicated that the formation of these rutin–MGO adducts remarkably reduced the toxicity of MGO, which provide further promise for the application of rutin as a scavenger of dicarbonyl compounds by dietary supplement and addition in foods.